Valores e atitudes sobre os papéis de gênero na Polícia Militar do Paraná - Souza, Marcos Aparecido de (2014)
This research investigates the values and attitudes of police officers as to gender roles within the socio- political and cultural Military Police of Paraná (PMPR) structure, and consequently the absence of women in certain areas, as well as the resistance and conflict in relation to changes in the occupations of those places almost exclusive to either sex. After more than thirty years of the entry of the first group of military officers in our state, we need to ask ourselves: how are gender roles in PMPR? In order to seek answers to these and other important questions, we developed this study was to diagnose through the application of a survey, what they think the military police on gender roles. The main questions that guide this study are: a) the extent to which the attributes of the genera are recognized as one sex or the other, and how they imply the division of roles between the genders among bureaucratic activity and operational service street within the Police? b) For this or that service, are really necessary attributes to be construed as exclusive or increased expression of either sex? c) Understanding the possession or absence of certain physical or psychological attributes influence the recognition of a hierarchy of men over women or homosexual? d) Because of that, there would be an overestimation of the operational activity of the street instead of bureaucratic activities? e) As PMPR in relation to other institutions or areas, is perceived by genres as regards the guarantees of human dignity and equal rights? f) Values and attitudes related to gender roles are the product of a police culture or reflects a broader culture? g) Finally, what are the public policies that influence positively towards greater gender equality in this context? The first chapter was constructed with concern over the fact of how, being a man or being a woman influences as a condition of recognition of the capacity of developing certain police roles. In the second chapter, we sought to investigate three explanatory lines that could assist us in understanding the values and attitudes regarding gender roles in PMPR. The first relates to theories of male dominance and the theory of the scientific field ; the second explanatory line was towards the investigation of principles developed by the canons of Western thought and that formed the basis for the structuring of modern institutions ; the third row , regards it as a police culture , based on studies done by the American police . The third chapter will be assigned to research methodology; we describe its development through the quantitative method and using the Survey tool to collect data, their applicability, methods, advantages and limitations. The fourth chapter was reserved for the analysis of data collected in the survey on values , attitudes and gender roles in PMPR within a similar set of issues in order to ensure standards and trends through analysis of indexes and comparisons with other research like.